Emulation, indebtedness and income distribution: A monetary theory of production approach - Guglielmo Forges Davanzati; Andrea Pacella (Intervention. European Journal of Economics and Economic Policies, 2010)
The aim of this paper is to study the effect of emulation within a basic schema of the monetary theory of production (MTP). A theoretical model is presented, where workers set their target level of consumption based on the comparison with other workers taken as reference. It is shown that emulation can play a crucial role in increasing workers' propensity to indebtedness. As a result, profits increase and so does the price level, thus generating a decline of the real wage. Moreover, the existence of indebtedness can provide a further solution to the socalled »paradox of profits« within the MTP.
Keywords: D71; E12; E21; J31; 330; monetary circuit; emulation; indebtedness; profits; wages